Description of the male of Architis catuaba Santos & Nogueira, 2008 and new records of Architis capricorna Carico, 1981 (Araneae: Pisauridae) - Silva, Estevam L. Cruz Da (Zootaxa, 2013)
The genus Architis Simon, 1898 currently includes 21 described species distributed in the Neotropical region, from Panama to Argentina (Platnick 2012). Santos (2007b) provided the latest revision, describing eight new species and synonymizing A. nitidopilosa Simon, 1898 with A. tenuis Simon, 1898 (the type species of the genus), A. suarez Carico, 1989 with A. cymatilis Carico, 1981 and A. paulistana Mello-Leitão, 1917 with Aglaoctenus lagotis (Holmberg, 1876). Recently, three new species were described by Santos & Nogueira (2008) from the Amazonian region, inNorthern Brazil.